Nano‐droplet formation in fragrance tinctures. (4th June 2013) - Marcus, Julien; Klossek, Michael L; Touraud, Didier; Kunz, Werner
ABSTRACT Recently it was shown that water–ethanol–long‐chain alcohol mixtures can be significantly structured in a wide range of compositions. This work is an extension of these studies and suggests that some formulated products on the market correspond to these mixtures. We consider the domains of existence of the clear and homogeneous phase of four water–ethanol–perfumery molecules systems, the perfumery molecules being citronellol, citral, geranyl acetate and limonene, as they can be found in perfumery formulations. Dynamic and static light scattering experiments reveal also the presence of nano‐droplets in these ternary tincture systems. Based on these results the presence of nano‐droplets can be expected in Eau de Toilette, Eau de Parfum, and possibly in perfumes. Copyright © 2013 John Wiley & Sons, Ltd.